Hollow polyhedral NiS2 / Cu7. 2S4 sodium battery composite material as well as preparation method and application thereof
By building a hollow polyhedral structure and introducing the Kirkendal diffusion effect, the conductivity and cyclic stability of nickel sulfide materials are improved, and the problems of low conductivity and volume expansion of nickel sulfide in sodium ion batteries are solved, and the sodium battery is realized Excellent performance.
Patent Information
- Application Number
- CN202411278140.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-12
AI Technical Summary
The conductivity of nickel sulfide in sodium ion batteries is low and volume expansion leads to a shortening of cycle life, and the prior art is difficult to effectively improve its mechanical stability and conductivity.
By constructing a hollow polyhedral structure and introducing the Kirkendal diffusion effect, NiS2/Cu7.2S4 composite materials are synthesized using nickel nitrate, copper chloride and sulfur powder to form a built-in electric field to improve electron diffusion kinetics and conductivity.
The cyclic stability and electrochemical performance of nickel sulfide materials have been significantly improved, and good magnification and cyclic performance in sodium batteries have been achieved. The discharge specific capacity remains high under high current density.
Smart Images

Figure CN119252911A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a hollow polyhedron NiS2 / Cu 7.2 S4 sodium battery composite material and its preparation method and application. Background Art
[0002] In recent years, the consumption of fossil energy has continued to grow, which conflicts with the goal of green and sustainable development. The gradual depletion of fossil energy forces us to find energy storage materials with higher performance. Secondary batteries are considered to be energy storage devices that can be widely used in environmentally friendly vehicles, power storage and power fields. Among them, lithium-ion batteries have been widely used due to their high energy density, high window voltage, light weight and no self-discharge. However, with wider applications, the demand for lithium resources is inconsistent with its abundance on the surface, so the cost of lithium has risen accordingly. At this time, sodium-ion batteries, which are in the same family as lithium and have similar chemical properties, make it possible for sodium-ion batteries to replace and supplement lithium-ion batteries. As a key component of the battery, the electrode material directly affects the performance of the sodium-ion battery. The development of electrode materials with excellent performance can make the commercialization of sodium-ion batteries possible. Among them, the research on negative electrode materials mainly focuses on intercalation materials based on carbon-based materials, conversion reaction materials based on transition metal oxides / sulfides, and alloy reaction materials.
[0003] Transition metal sulfides have higher conductivity and higher specific capacity based on conversion reactions than their oxides, and are a potential electrode material. Nickel sulfides are rich in variety, have a high theoretical specific capacity, and show high electrochemical reversibility in the application of negative electrode materials for sodium ion batteries. However, nickel sulfide itself has low conductivity, and the volume expansion and material powderization caused by the conversion reaction mechanism greatly shorten the long cycle life of the electrode material. Therefore, it is crucial to improve the mechanical stability and conductivity of the material. Generally, the cyclic strain force is released by constructing a special microstructure, such as a hollow structure, a yolk shell structure, etc. The existence of a heterojunction structure will introduce a built-in electric field, which is generally considered to be a common means of improving conductivity. The Kirkendall effect refers to the formation of defects in the diffusion process of two metals with different diffusion rates, and then hollow nanoparticles are prepared. Therefore, the heterojunction establishment and hollow structure construction can be synergistically introduced into the built-in electric field through the Kirkendall effect. It can be seen that the reasonable design of the material structure and the construction of the heterojunction can improve the performance of nickel sulfide in sodium ion batteries, thereby realizing its application in the field of sodium ion batteries.
[0004] In summary, the present invention combines metal ion doping and structural construction, and prepares nickel nitrate, copper chloride and sulfur powder by high temperature and high pressure to obtain the corresponding solid polyhedron NiS2 / Cu 7.2According to the Kirkendall diffusion effect, by adjusting the ratio of different metal contents, different degrees of hollow polyhedron NiS2 / Cu are formed under high temperature environment. 7.2 This hollow structure is conducive to releasing the mechanical stress generated by the material during the cycle, thereby alleviating the inherent volume expansion problem of sulfide materials and ensuring the cyclic stability of the material during sodium storage. 7.2 The existence of the S4 heterojunction constructs a built-in electric field, which promotes electron transport, improves the electrical conductivity and promotes the diffusion dynamics of electrons, thereby improving the electrochemical properties of sulfide materials. Summary of the invention
[0005] In view of the above shortcomings of the prior art, the present invention provides a hollow polyhedron NiS2 / Cu 7.2 S4 sodium battery composite material and its preparation method and application. The present invention constructs a special hollow polyhedron structure, which is conducive to releasing the stress generated by the sulfide material during the cycle, slowing down the volume expansion of the sulfide material during the sodium insertion / extraction process, and improving the cycle stability of the sulfide material; in addition, NiS2 / Cu 7.2 The presence of the S4 heterojunction introduces a built-in electric field, which accelerates electron diffusion and improves the diffusion kinetics of electrons, thereby improving the electrochemical properties of sulfide materials.
[0006] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0007] A hollow polyhedron NiS2 / Cu 7.2 The S4 sodium battery composite material has a hollow polyhedron morphology and is prepared by the following method: nickel nitrate, copper chloride, and sulfur powder are used as raw materials to generate solid polyhedron NiS2 / Cu 7.2 S4 complex, and then calcined at high temperature to obtain hollow polyhedron NiS2 / Cu 7.2 S4(NiS2 / Cu 7.2 S4 is referred to as NCSs) sodium battery composite material; the molar ratio of nickel nitrate, copper chloride and sulfur powder is 2:1:6.
[0008] The present invention uses nickel nitrate, copper chloride and sulfur powder to obtain the corresponding solid polyhedron NiS2 / Cu by simple hydrothermal reaction. 7.2 S4 complex, and then based on the Kirkendall diffusion effect, by adjusting the content ratio of different metals, the hollow polyhedron NiS2 / Cu is formed in different degrees under high temperature environment. 7.2 S4 sodium battery composite material. Hollow polyhedron NiS2 / Cu 7.2The S4 sodium battery composite material has the best structure and morphology. The hollow polyhedron structure is conducive to releasing the mechanical stress generated by the sulfide material during the cycle, thereby alleviating the inherent volume expansion problem of the sulfide material and ensuring the cycle stability of the sulfide material during the sodium storage process; in addition, the hollow polyhedron NiS2 / Cu 7.2 NiS2 / Cu in S4 sodium battery composites 7.2 The presence of the S4 heterojunction creates an internal electric field that can promote electron transport, improve the conductivity and promote the diffusion kinetics of electrons, thereby improving the electrochemical properties of sulfide materials. 7.2 The S4 sodium battery composite material has good rate performance and excellent cycle performance. When applied to the negative electrode material of sodium battery, the assembled half-cell has a discharge specific capacity of 566.3 mAh / g after 100 cycles at a current density of 0.1 A / g; and still has a discharge specific capacity of 443.7 mAh / g after 10,000 cycles at a high current density of 10 A / g.
[0009] Preferably, the hollow polyhedron NiS2 / Cu 7.2 The diameter of the S4 sodium battery composite material is 300~400 nm.
[0010] The hollow polyhedron NiS2 / Cu 7.2 The preparation method of the S4 sodium battery composite material comprises the following steps:
[0011] S1. Add an appropriate amount of polyvinyl pyrrolidone (PVP) to ethylene glycol and disperse it evenly. Then add nickel nitrate, copper chloride and sulfur powder to the solution in sequence. After mixing evenly, perform hydrothermal reaction at 120-180 °C for 10-18 h. After washing, separation and drying, solid polyhedron NiS2 / Cu 7.2 S4 complex;
[0012] S2. The solid polyhedron NiS2 / Cu obtained in step S1 7.2 The S4 composite was calcined at 450-600 °C for 2-3 h in an inert gas atmosphere to obtain a hollow polyhedron NiS2 / Cu 7.2 S4 sodium battery composite material.
[0013] The hollow polyhedron NiS2 / Cu 7.2 The S4 sodium battery composite material is prepared by a simple hydrothermal reaction and high temperature calcination. In step S1, a solid polyhedron NiS2 / Cu 7.2S4 composite, wherein different types of metal salts will affect the external morphology of the final composite material; in step S2, under the protection of an inert gas atmosphere, the solid polyhedron NiS2 / Cu 7.2 The S4 complex is kept at high temperature for a certain period of time, and according to the Kirkendall effect, the ratio of different types of metal sources is adjusted to form hollow polyhedron NiS2 / Cu 7.2 S4 sodium battery composite material.
[0014] Preferably, in step S1, the molecular weight of the polyvinyl pyrrolidone is 58000, and the concentration of polyvinyl pyrrolidone in ethylene glycol is 3.3-15 g / L; the concentration of the nickel nitrate in ethylene glycol is 0.02-0.18 mol / L.
[0015] Preferably, in step S2, the high temperature calcination temperature is 500-600°C.
[0016] The present invention also provides the hollow polyhedron NiS2 / Cu 7.2 Application of S4 sodium battery composite materials in sodium ion battery negative electrode materials.
[0017] Compared with the prior art, the present invention is beneficial in that:
[0018] (1) The hollow polyhedron structure constructed by the present invention can release the mechanical stress generated by the sulfide material during the cycle, thereby alleviating the inherent volume expansion problem of the sulfide material and ensuring the cycle stability of the sulfide material during the sodium storage process; in addition, due to the hollow polyhedron NiS2 / Cu 7.2 NiS2 / Cu in S4 composites 7.2 The existence of the S4 heterojunction constructs a built-in electric field, which can promote electron transport and promote the diffusion dynamics of electrons while improving conductivity.
[0019] (2) Hollow polyhedron NiS2 / Cu prepared by the present invention 7.2 The S4 sodium battery composite material has good rate performance and excellent cycle performance. When applied to the negative electrode material of sodium battery, the assembled half-cell has a discharge specific capacity of 566.3 mAh / g after 100 cycles at a current density of 0.1 A / g, and still has a discharge specific capacity of 443.7 mAh / g after 10,000 cycles at a high current density of 10 A / g.
[0020] (3) The present invention prepares hollow polyhedron NiS2 / Cu by simple hydrothermal reaction and high temperature calcination 7.2 The S4 sodium battery composite material has a simple preparation process, the equipment and devices used are all conventional equipment and devices, and the raw material cost is low, which is conducive to industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the XRD pattern of the hollow polyhedron NCSs sodium battery composite material prepared in Example 1;
[0022] Figure 2 This is a SEM image of the hollow polyhedron NCSs sodium battery composite material prepared in Example 1;
[0023] Figure 3 TEM image of the hollow polyhedron NCSs sodium battery composite material prepared in Example 1;
[0024] Figure 4 This is a cycle performance diagram of the hollow polyhedron NCSs sodium battery composite material prepared in Example 1 at a current density of 0.1 A / g;
[0025] Figure 5 This is a cycling performance diagram of the hollow polyhedron NCSs sodium battery composite material prepared in Example 1 at a current density of 10 A / g;
[0026] Figure 6 TEM image of the NSs sodium battery material prepared in Comparative Example 1;
[0027] Figure 7 TEM image of the CNSs sodium battery composite material prepared in Comparative Example 2;
[0028] Figure 8 TEM image of the CSs sodium battery material prepared in Comparative Example 3;
[0029] Fig. 9 The cycle performance diagram of the hollow polyhedron NCSs sodium battery composite material prepared in Example 1 at different current densities;
[0030] Fig.10 This is a comparison chart of the cycle performance of the NSs sodium battery material prepared in Comparative Example 1, the CNSs sodium battery composite material prepared in Comparative Example 2, and the CSs sodium battery material prepared in Comparative Example 3 at a current density of 0.1 A / g;
[0031] Fig.11 This is a cycling performance diagram of the hollow spherical NCSs-C sodium battery composite material prepared in Comparative Example 4 at a current density of 10 A / g. DETAILED DESCRIPTION
[0032] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The present invention provides a hollow polyhedron NiS2 / Cu 7.2 The S4 sodium battery composite material has a hollow polyhedron morphology and is prepared by the following method: nickel nitrate, copper chloride, and sulfur powder are used as raw materials to generate solid polyhedron NiS2 / Cu 7.2 S4 complex, and then calcined at high temperature to obtain hollow polyhedron NiS2 / Cu 7.2 S4(NiS2 / Cu 7.2 S4 is referred to as NCSs) sodium battery composite material; the molar ratio of nickel nitrate, copper chloride and sulfur powder is 2:1:6.
[0034] The hollow polyhedron NiS2 / Cu 7.2 The diameter of the S4 sodium battery composite material is 300~400 nm.
[0035] The hollow polyhedron NiS2 / Cu 7.2 The preparation method of the S4 sodium battery composite material comprises the following steps:
[0036] S1. Add an appropriate amount of polyvinyl pyrrolidone to ethylene glycol and disperse it evenly. Then add nickel nitrate, copper chloride and sulfur powder to the solution in sequence. After mixing evenly, perform hydrothermal reaction at 120-180 °C for 10-18 h. After washing, separation and drying, solid polyhedron NiS2 / Cu 7.2 S4 complex;
[0037] S2. The solid polyhedron NiS2 / Cu obtained in step S1 7.2 The S4 composite was calcined at 450-600 °C for 2-3 h in an inert gas atmosphere to obtain a hollow polyhedron NiS2 / Cu 7.2 S4 sodium battery composite material.
[0038] In some examples, the concentration of polyvinyl pyrrolidone in ethylene glycol is 3.3-15 g / L; the concentration of nickel nitrate in ethylene glycol is 0.02-0.18 mol / L.
[0039] In the following specific examples, the molecular weight of the polyvinyl pyrrolidone is 58,000.
[0040] Example 1
[0041] A hollow polyhedron NiS2 / Cu 7.2 S4 sodium battery composite material, preparation steps are as follows:
[0042] S1. Dissolve 0.4 g PVP in 50 mL ethylene glycol, stir evenly by ultrasonication to form solution A, add 2 mmol nickel nitrate hexahydrate, 1 mmol copper chloride dihydrate, and 6 mmol sulfur powder to solution A in sequence and stir until evenly mixed to obtain mixed solution A; place mixed solution A in a reactor and heat to 180 °C for hydrothermal reaction for 12 h; wash the obtained precipitate with deionized water and anhydrous ethanol by centrifugation four times respectively, and then vacuum dry to obtain a solid polyhedral NCSs complex;
[0043] S2. The solid polyhedral NCSs solid was placed in a tubular furnace filled with argon, heated to 600 °C at a heating rate of 3 °C / min and kept at this temperature for 3 h to obtain a hollow polyhedral NCSs sodium battery composite material.
[0044] Figure 1 The XRD pattern of the hollow polyhedron NCSs sodium battery composite material prepared in Example 1 shows that the diffraction peak is at 27.1 o ,31.4 o ,35.3 o ,38.8 o , and 45.1 o , corresponding to the (1 1 1), (2 0 0), (2 1 0), (2 1 1) and (2 2 0) planes of NiS2 (JCPDS No.89-7142), with the diffraction peak at 27.7 o ,32.1 o ,45.9 o , corresponding to Cu 7.2 S4 (JCPDS No.72-1966)'s (1 1 1), (2 0 0) and (2 2 0) faces; XRD results show that the hollow polyhedral NCSs sodium battery composites have been successfully synthesized. Figure 2 3 are SEM and TEM images of the hollow polyhedron NCSs sodium battery composite material prepared in Example 1, respectively. Figure 2 As can be seen from Figure 3, the hollow polyhedral NCSs sodium battery composite material is polyhedral in shape, with a loose hollow structure inside and a diameter between 300 and 400 nm.
[0045] Comparative Example 1
[0046] A NSs sodium battery material, the preparation steps are as follows:
[0047] S1. Dissolve 0.4 g PVP in 50 mL ethylene glycol and stir it evenly by ultrasonic to form solution A. Then, dissolve 3 mmol nickel nitrate hexahydrate and 6 mmol sulfur powder in solution A and stir until evenly to obtain mixed solution A. Place mixed solution A in a reactor and heat it to 180 °C for hydrothermal reaction for 12 h. Wash the obtained precipitate with deionized water and anhydrous ethanol by centrifugation four times respectively, and then vacuum dry it to obtain solid NSs.
[0048] S2. Place the solid NSs solid in a tubular furnace filled with argon, heat it to 600 °C at a heating rate of 3 °C / min and keep it at that temperature for 3 h to obtain NSs sodium battery material.
[0049] Figure 6 This is the TEM image of the NSs sodium battery material prepared in Comparative Example 1. It can be seen that the morphology of the monomer NSs sodium battery material is similar to the hollow polyhedron NCSs sodium battery composite material prepared in Example 1, but there is no obvious hollow structure.
[0050] Comparative Example 2
[0051] A CNSs sodium battery composite material, the preparation steps are as follows:
[0052] S1. 0.4 g PVP was dissolved in 50 mL ethylene glycol, and ultrasonically stirred to form solution A. 1 mmol nickel nitrate hexahydrate, 2 mmol copper chloride dihydrate, and 6 mmol sulfur powder were dissolved in the solution A in sequence and stirred to obtain mixed solution A. The mixed solution A was placed in a reactor and heated to 180 °C for hydrothermal reaction for 12 h. The obtained precipitate was washed four times with deionized water and anhydrous ethanol respectively by centrifugation, and then vacuum dried to obtain a solid CNSs complex.
[0053] S2. The solid CNSs solid was placed in a tubular furnace filled with argon, heated to 600 °C at a heating rate of 3 °C / min and kept at this temperature for 3 h to obtain a CNSs sodium battery composite material.
[0054] Figure 7 This is the TEM image of the CNSs sodium battery composite material prepared in Comparative Example 2. It can be seen from the figure that when the molar amount of copper chloride is greater than the molar amount of nickel nitrate, the morphology of the obtained CNSs sodium battery composite material changes significantly, presenting an internal loose and porous micron sphere structure with a diameter of about 2~3 μm.
[0055] Comparative Example 3
[0056] A CSs sodium battery material preparation step is as follows:
[0057] S1. Dissolve 0.4 g PVP in 50 mL ethylene glycol and stir it evenly by ultrasonic to form solution A. Dissolve 3 mmol copper chloride dihydrate and 6 mmol sulfur powder in the solution A and stir until evenly to obtain mixed solution A. Heat the mixed solution A in a reactor to 180 °C for hydrothermal reaction for 12 h. Wash the obtained precipitate with deionized water and anhydrous ethanol by centrifugation four times respectively, and then dry it in vacuum to obtain solid CSs.
[0058] S2. Place the solid CSs solid in a tubular furnace filled with argon, heat it to 600℃ at a heating rate of 3℃ / min and keep it at that temperature for 3 h to obtain CSs sodium battery material.
[0059] Figure 8 This is a TEM image of the CSs sodium battery material prepared in Comparative Example 3. It can be seen from the figure that the morphology of the monomer CSs sodium battery material is similar to that of the CNSs sodium battery composite material prepared in Comparative Example 2, but the interior is denser than that of the CNSs sodium battery composite material.
[0060] Comparative Example 4
[0061] A NCSs-C sodium battery composite material, the preparation steps are as follows:
[0062] S1. Dissolve 0.4 g PVP in 50 mL ethylene glycol and stir to form solution A by ultrasonic stirring. Dissolve 2 mmol nickel sulfate hexahydrate, 1 mmol copper chloride dihydrate, 3 mmol thiourea and 3 mmol sublimed sulfur in the solution A and stir to obtain mixed solution A. Place the mixed solution A in a reactor and heat to 180 °C for hydrothermal reaction for 12 h. Wash the obtained precipitate with deionized water and anhydrous ethanol by centrifugation four times respectively, and then obtain solid spherical NCSs-c after vacuum drying.
[0063] S2. The solid spherical NCSs-c solid was placed in a tubular furnace filled with argon, heated to 600 °C at a heating rate of 3 °C / min and kept at this temperature for 3 h to obtain a hollow spherical NCSs-C sodium battery composite material.
[0064] Application Examples
[0065] The materials prepared in Example 1 and Comparative Examples 1 to 4, the conductive agent (Super P), and carboxymethyl cellulose (CMC) were mixed uniformly at a mass ratio of 7: 2: 1, and an appropriate amount of ultrapure water was added to form a slurry, which was coated on a copper foil using a scraper to form a negative electrode sheet; the coated copper foil was placed in a drying oven at 80 ° C and dried for 12 h, and then the copper foil coated with the material was cut into small discs with a diameter of 12 mm, and placed in a glove box to assemble a button battery (CR2032). The negative electrode sheet made of the composite material was used as the working electrode, and the sodium block was used as the counter electrode to test its electrochemical performance, wherein the diaphragm used Whatman GF / A, and the electrolyte system was 1M NaF6 solute and 100% DME solvent.
[0066] The assembled button batteries were subjected to electrochemical performance tests. The test instrument used for the electrochemical performance tests was the LANHE-CT2001A multi-channel battery testing system produced by Wuhan Landian Electronics Co., Ltd. The static time was 12 h, the voltage window range was: 0.2-2.8 V, the current density range was: 100-10000 mA / g, and the cycle number range was: 100-10000 times.
[0067] Figure 4 This is the cycle performance diagram of the hollow polyhedron NCSs sodium battery composite material prepared in Example 1 at a current density of 0.1 A / g. Figure 4 It can be seen that the hollow polyhedron NCSs sodium battery composite material still maintains a discharge specific capacity of up to 566.3 mAh / g after 100 cycles, indicating that it has good cycle stability. Figure 5 The cycle performance diagram of the hollow polyhedron NCSs sodium battery composite material prepared in Example 1 at a current density of 10 A / g. Figure 5 It can be seen that the hollow polyhedron NCSs sodium battery composite material still has a discharge specific capacity of 443.7 mAh / g after 10,000 cycles, reflecting its good rate performance and excellent cycle performance.
[0068] Fig. 9 The cycle performance diagram of the hollow polyhedron NCSs sodium battery composite material prepared in Example 1 at different current densities; Fig.10 The cyclic performance comparison chart of the NSs sodium battery material prepared in Comparative Example 1, the CNSs sodium battery composite material prepared in Comparative Example 2, and the CSs sodium battery material prepared in Comparative Example 3 at a current density of 0.1 A / g is shown; Comprehensive comparison Fig. 9 and Fig.10 It can be seen that the hollow polyhedron NiS2 / Cu prepared by the present invention 7.2 The S4 sodium battery composite material has the best cycle performance.
[0069] Fig.11 The cycle performance diagram of the hollow spherical NCSs-C sodium battery composite material prepared in Comparative Example 4 at a current density of 10 A / g is shown in FIG. Fig.11 It can be seen that the discharge specific capacity of the composite material decays to 208.5 mAh / g after 2000 cycles.
[0070] In summary, the present invention adjusts the types of raw materials and the ratio between them to control the microscopic morphology and hollowness of the composite material, so that the prepared hollow polyhedron composite material has the best structure and morphology; the hollow polyhedron NiS2 / Cu prepared by the present invention 7.2 The hollow structure in the S4 sodium battery composite material can alleviate the volume expansion problem during the material cycle, making it have the best cycle stability. In addition, the NiS2 / Cu 7.2 The presence of the S4 heterojunction can introduce a built-in electric field to improve the conductivity and electron diffusion kinetics, which is beneficial to the sodium storage kinetics process. 7.2 The S4 sodium battery composite material is used in the negative electrode material of sodium battery. The assembled half-cell has good rate performance and excellent cycle performance. After 100 cycles at a current density of 0.1 A / g, it has a discharge specific capacity of 566.3 mAh / g, and after 10,000 cycles at a high current density of 10 A / g, it still has a discharge specific capacity of 443.7 mAh / g.
[0071] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A hollow polyhedron NiS2 / Cu 7.2 S4 sodium battery composite material, characterized in that It has a hollow polyhedron morphology and is prepared by the following method: nickel nitrate, copper chloride, and sulfur powder are used as raw materials to generate solid polyhedron NiS2 / Cu by hydrothermal reaction. 7.2 S4 complex, and then calcined at high temperature to obtain hollow polyhedron NiS2 / Cu 7.2 S4 sodium battery composite material; the molar ratio of nickel nitrate, cupric chloride and sulfur powder is 2:1:
6.
2. A hollow polyhedron NiS2 / Cu according to claim 1 7.2 S4 sodium battery composite material, characterized in that The hollow polyhedron NiS2 / Cu 7.2 The diameter of the S4 sodium battery composite material is 300~400 nm.
3. A hollow polyhedron NiS2 / Cu as claimed in any one of claims 1 to 2 7.2 The preparation method of the S4 sodium battery composite material comprises the following steps: S1. Add an appropriate amount of polyvinyl pyrrolidone to ethylene glycol and disperse it evenly. Then add nickel nitrate, copper chloride and sulfur powder to the solution in sequence. After mixing evenly, perform hydrothermal reaction at 120-180 °C. After washing, separation and drying, solid polyhedron NiS2 / Cu 7.2 S4 complex; S2. The solid polyhedron NiS2 / Cu obtained in step S1 7.2 The S4 composite was calcined at 450-600 °C in an inert gas atmosphere to obtain a hollow polyhedron NiS2 / Cu 7.2 S4 sodium battery composite material.
4. The hollow polyhedron NiS2 / Cu according to claim 3 7.2 The preparation method of S4 sodium battery composite material is characterized in that: In step S1, the molecular weight of the polyvinyl pyrrolidone is 58000, and the concentration of the polyvinyl pyrrolidone in ethylene glycol is 3.3-15 g / L; the concentration of the nickel nitrate in ethylene glycol is 0.02-0.18 mol / L.
5. The hollow polyhedron NiS2 / Cu according to claim 3 7.2 The preparation method of S4 sodium battery composite material is characterized in that: In step S1, the hydrothermal reaction time is 10 to 18 hours.
6. The hollow polyhedron NiS2 / Cu according to claim 3 7.2 The preparation method of S4 sodium battery composite material is characterized in that: In step S2, the high temperature calcination temperature is 500-600°C, and the high temperature calcination time is 2-3 hours.
7. The hollow polyhedron NiS2 / Cu according to any one of claims 1 to 2 7.2 Application of S4 sodium battery composite materials in sodium ion battery negative electrode materials.
Citation Information
Patent Citations
Cobaltosic sulfide and nickel disulfide / carbon composite material and preparation method and application thereof in sodium ion battery
CN116470029A
Preparation method of sulfur-nitrogen co-doped carbon-coated modified Cu1.96S / NiS hollow microspheres
CN116525777A
Hollow nanocube In2S3 / CoS2atNC composite material as well as preparation method and application thereof
CN117747799A
